PENDETEKSIAN MANAJEMEN LABA RIIL DI INDONESIA (Studi Empiris pada Perusahaan yang Melakukan Right Issue Antara Tahun 2011-2015 Dan Terdaftar Di BEI) - Christyansah, Galih Ivan (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aims is to detect the earnings management through manipulation of real activity  in  the  company  that  plans  to  offer additional  shares  rights  issue.  Earnings management  is  measured using  three  proxies  manipulation  of  real  activity,  namely  the activity of cash flow operating activities, costs of production, and through discretionary costs.   Real   activity   manipulation   model  that  used   in   this   study   is   based   on   the Roychowdhury’s model (2006).The data used in this research is secondary data in the form of financial statements. The population in this study are all companies listed on the Indonesia Stock Exchange by using samples selected through purposive sampling method. Regression analysis was used to find the abnormal value estimate of operating cash flow, production costs, and discretionary costs. The results showed that company was not indicated to use real earnings management activity  by  lowering the  operating  cash  flow,   raising  production  costs,  and  lower discretionary costs. The Company is not indicated to use real earnings management activity can be caused the management of companies prefer to use accrual earnings management activity.Keywords: Earnings management, real activities manipulation, right issue